Oyster Mushroom Cultivation Training as Empowerment Program for Students of Foundation of Islamic Education and Social “Ar-Rohmah” - Rufiani Nadzirah; Dyah Ayu Savitri; Noer Novijanto (Warta Pengabdian, 2022)
Oyster mushroom is one of the horticultural commodities in Indonesia. This community empowerment program through oyster mushroom cultivation is designed as an effort to provide a sense of equality, partnership, and togetherness for the improvement of the community's economy. Islamic and Social Education Foundation "Ar-Rohmah" with its abundant natural and human resource potential, can be a part of the process of social change. Student empowerment at this foundation manages students to do something beneficial for the community, including through training programs and mentoring in oyster mushroom (Pleurotus spp) cultivation. Accompanied by the Institute for Research and Community Service (LP2M) Team at the University of Jember, this activity was carried out to the students of the "Ar-Rohmah" Islamic and Social Education Foundation in Suren village, Ledokombo District, Jember through the presentation of theory and field practice on cultivation. mushrooms. This community service activity will form a small industry that is able to provide income for students of the "Ar-Rohmah" Islamic and Social Education Foundation in Suren Village, Ledokombo District, Jember. During the execution of program, students were showing high antusiams toward prospect and cultivation technology of oyster mushroom by giving contributions, suggestions and creative ideas.